1983
DOI: 10.2134/agronj1983.00021962007500050009x
|View full text |Cite
|
Sign up to set email alerts
|

Corn Growth Response to Temperature and Photoperiod II. Leaf‐Initiation and Leaf‐Appearance Rates1

Abstract: The prediction of evapotranspiration and canopy photosynthesis, for example in crop simulation modeling and in remote sensing applications, requires a quantitative description of the influence of environmental factors such as temperature and photoperiod on leaf area development. The objectives of this study were to define the temperature response curves and the responses to photoperiod for two components of leaf area development in corn (Zea mays L.), namely leaf‐initiation rate and leaf‐appearance rate. Plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
94
1
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(107 citation statements)
references
References 14 publications
10
94
1
2
Order By: Relevance
“…At moderately-low temperature, minimum and maximum values ranged from 8 to 10 with an average of 9, whereas leaf number varied from 10 to 12 with an average of 11 leaves plant −1 at optimum temperature. These observed temperature effects on corn growth and development are in agreement with previous findings made by Warrington and Kanemasu (1983) and Li et al (2008). They found a curvilinear reduction of new leaf appearance rate in cold-stressed corn seedlings than plants grown under optimum temperature conditions.…”
Section: Resultssupporting
confidence: 92%
“…At moderately-low temperature, minimum and maximum values ranged from 8 to 10 with an average of 9, whereas leaf number varied from 10 to 12 with an average of 11 leaves plant −1 at optimum temperature. These observed temperature effects on corn growth and development are in agreement with previous findings made by Warrington and Kanemasu (1983) and Li et al (2008). They found a curvilinear reduction of new leaf appearance rate in cold-stressed corn seedlings than plants grown under optimum temperature conditions.…”
Section: Resultssupporting
confidence: 92%
“…In cereal crops, Yin and Kropff ( 1996) showed that the rate in rice decreased gradually during vegetative growth, and Warrington and Kanemasu ( 1983) reported that the rate in maize was constant from planting to the emergence of the 12th leaf. In dicotyledons, the rate in cotton increased with time before the appearance of the 9th leaf and became con- stant after the appearance of the lOth leaf (Reddy et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Delay in sowing wheat resulted in less TDM, which might be due to sub-optimal growing conditions during the vegetative growth phase (Farooq and Cheema, 2014). Leaf development and dry matter accumulation greatly depend on the prevailing temperature and unfavorable temperature (which is common in late sowing) negatively influences vegetative growth (Warrington and Kanemasu, 1983).…”
Section: Discussionmentioning
confidence: 99%